Role of Nanobiotechnology Towards Agri-Food System - Niguse Hotessa Halake; Jara Muda Haro (Journal of Nanotechnology)
The major challenge of modern agriculture is to satisfy actual and future global food demands efficiently. This great challenge requires combined efforts to preserve natural resources to support intensive agriculture while limiting detrimental impacts on the environment. One of these efforts is using nanobiotechnology. Nanobiotechnology is the application of nanotechnology in biological science. Nanotechnology is the science of manipulating materials at the nanoscale (1 nm = 10ˉ⁹ m). This review summarizes the potential of nanobiotechnology for its importance in increasing yield in agriculture and providing consumers with quality and contamination-free food. In the agriculture sector, nanobiotechnology is necessarily used as fertilizers (nanofertilizers) for crop yield improvement, pesticides (nanopesticides) for crop protection, and nanobiosensors for the detection of crop pathogens, soil conditions, and vegetation conditions, Similarly, intelligent food packaging, and detection of pathogens, adulterants, and toxins in food are its importance in the food sector.